Study of phase evolution and dielectric properties of Sn-doped barium titanate. Issue 1 (22nd May 2017) - Ansaree, Md. Jawed; Upadhyay, Shail
Abstract : The reaction of barium carbonate (BaCO3 ) with titanium dioxide (TiO2 ) was studied by simultaneous thermogravimetric and differential scanning calorimetric analysis up to 1000°C. Based on the results of thermal analysis, three compositions ( x = 0·00, 0·05 and 0·15) of the BaTi1− x Sn x O3 system were synthesized by calcination at 1000 and 1100°C and sintering at 1350°C. The effect of calcination temperature on the phase formation of these samples was investigated by recording X-ray diffraction patterns. The single-phase tetragonal barium titanate (BaTiO3 ) was obtained at 1100°C. Analysis of the X-ray diffraction studies of samples x = 0·05 and 0·15 confirmed that the formation of single-phase solid solutions BaTi0·95 Sn0·05 O3 and BaTi0·85 Sn0·15 O3 takes place by way of formation of barium titanate and barium stannate (BaSnO3 ) phases and a reaction between them at temperature >1100°C. The percentage formation of single-phase solid solution and the lattice parameter increase with increasing calcination temperature. The phase purity of the obtained powders was also examined using Fourier transform infrared spectroscopy. Morphological and compositional analyses of the samples were performed using scanning electron microscopy and energy-dispersive X-ray analysis, respectively. Dielectric constant and dissipation factor of the samples were measured in the temperature range of 100 to 200°C and frequency range of 50 Hz–2 MHz.